CYTOKINE STATUS IN HIV INFECTED WOMEN WITH INFLAMMATORY DISEASES OF THE GENITALS - Olimova Nasiba Ismatulloyevna (International Engineering Journal For Research & Development, 2020)
The aim of the study was to study the cytokine profile in HIV-infected women with acute vaginitis during treatment Materials and methods- the study examined 35 women for 2019-2020 with HIV infection and 20 women who were conditionally healthy, a control group. The level of cytokines (IFNγ, IL-17) in the serum of peripheral blood was studied by enzyme-linked immunosorbent assay using test systems "Vector-Best" Results and discussion: the ratio of IFNγ / IL-17 (pro-inflammatory / anti-inflammatory cytokines or Tx1 / Tx2) in healthy women was 2.2. In the presence of a pronounced inflammatory process, that is, in women of the main group, this indicator was 0.96. After immunocorrecting treatment with the use of Imunorix in women with nonspecific vaginitis, IFNγ approached the control values, the content of IL-17, and after treatment did not normalize, remaining 5.5 times higher than in women of the control group, the ratio of IFNγ / IL-17. in women of the main group, after treatment, this indicator decreased to 0.42. Conclusion: A violation of the ratio of pro- and anti-inflammatory cytokines to talk about the presence of a previous immunodeficiency state and was manifested by the presence of complications in the presence of acute vaginitis.